Graphene thermal interface material with hierarchical pore structure and preparation method thereof

By introducing multi-stage pore structures into graphene thermal interface materials and using aminoguanidine carbonate as reducing agents, the problems of high cost and poor vertical thermal conductivity of graphene thermal interface materials are solved, and high-efficiency vertical thermal conductivity and low interface thermal conductivity are achieved The effect of resistance is suitable for large-scale industrial applications.

CN119176550AActive Publication Date: 2024-12-24ZHEJIANG ENJIE THERMAL MANAGEMENT TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411687538.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2024-12-24
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The application of graphene in the field of thermal interface materials faces the problems of high preparation costs, poor vertical thermal conductivity and high interface thermal resistance, especially in large-scale industrial applications.

Method used

Using graphene thermal interface material with multi-stage pore structure, the first-stage pores of 10~50nm, second-stage pores of 1~10μm and third-stage pores of 100~300μm are introduced into the wrinkles of the graphene sheet, combining aminoguanidine carbon As a reducing agent, acid salt is prepared by casting, scraping or spin coating to form an efficient vertical thermal conductive material.

Benefits of technology

It achieves a balance between high elasticity and high equivalent thermal conductivity, significantly reduces the interface thermal resistance, improves the cost-effectiveness and environmental friendliness of the materials, and is suitable for large-scale mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176550A_ABST
    Figure CN119176550A_ABST
Patent Text Reader

Abstract

The invention discloses a graphene thermal interface material with a hierarchical pore structure and a preparation method of the graphene thermal interface material. The graphene thermal interface material has a unique hierarchical pore distribution structure and realizes high compression resilience and low interface thermal resistance. According to the preparation method, the characteristics of slow reduction and self thermal foaming of aminoguanidine carbonate on graphene oxide are ingeniously utilized, after the aminoguanidine carbonate and graphene oxide are mixed and coated to form a composite film, slow reduction occurs in the drying process, so that graphene oxide sheets are cross-linked, and primary pores are formed along with moisture volatilization; in the low-temperature heat treatment, the aminoguanidine carbonate is decomposed at the temperature of 50-100 DEG C to generate gas, secondary pores are formed by the generated gas, and the graphene oxide at the temperature of 100 DEG C or above further loses oxygen-containing groups to promote formation of tertiary pores; finally, the pore structure is further developed under high-temperature treatment, and the final hierarchical pore structure is formed. The graphene material with the hierarchical pore structure has a high compression resilience characteristic, has an excellent caulking effect on a thermal interface, and has a wide application prospect in high-performance interface heat dissipation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of thermal interface materials, in particular to a graphene thermal interface material with a multi-level pore structure and a preparation method thereof. Background Art

[0002] As a two-dimensional material, graphene has shown great potential in the field of thermal interface materials with its unique structure and excellent physical and chemical properties. First, graphene has extremely high thermal conductivity and can quickly transfer heat, thereby effectively reducing the operating temperature of electronic equipment and improving its performance and stability. Secondly, the thickness of graphene is extremely thin, only a single layer or a few layers of atoms, which makes it almost not increase the volume and weight of the device when it is used. In addition, graphene has high mechanical strength and good flexibility, and can be easily processed into various shapes to meet the needs of different devices.

[0003] Although graphene has many advantages in the field of thermal interface materials, its practical application still faces some challenges. First, the preparation cost of graphene is high, especially large-area high-quality graphene films, which limits its popularity in large-scale industrial applications. Secondly, although graphene has extremely high thermal conductivity in the horizontal direction, its thermal conductivity in the vertical direction is low, and conventional high-oriented graphene films are difficult to give full play to the inherent advantages of graphene in thermal interface applications. Furthermore, the contact between the graphene film and the heat dissipation surface is usually rigid docking, which will lead to an increase in the thermal resistance of the interface, further limiting the heat dissipation performance in the vertical direction. In response to these problems, some studies have attempted to improve the problem of poor vertical thermal conductivity by introducing wrinkled structures, porous structures or vertically oriented structures, but they usually involve complex preparation processes and use environmentally unfriendly chemical reagents, which are difficult to promote on a large scale. Therefore, there are still many difficulties in developing a green, low-cost, high vertical thermal conductivity graphene thermal interface material. Summary of the invention

[0004] In view of the problems raised in the background technology, the present invention provides a graphene thermal interface material with a multi-level pore structure, which exhibits excellent compression resilience and high equivalent vertical thermal conductivity.

[0005] Specifically, the present invention adopts the following technical solutions: One of the technical solutions of the present invention is to provide a graphene thermal interface material with a multi-level pore structure, wherein the graphene thermal interface material is composed of wrinkled graphene sheets, with an overall thickness of 0.2-2 mm and a density of 0.08-0.32 g / cm 3The graphene thermal interface material contains primary pores with a size of 10-50 nm, secondary pores with a size of 1-10 μm, and tertiary pores with a size of 100-300 μm. The primary pores exist in the wrinkles of the graphene sheets, and the secondary and tertiary pores exist between the graphene sheets. The thermal impedance of the graphene thermal interface material at 50 psi is 0.02-0.2 K cm 2 / W.

[0006] Furthermore, in the graphene thermal interface material, the volume proportions of the primary pores, the secondary pores, and the tertiary pores are 16% to 28%, 35% to 42%, and 20% to 28%, respectively.

[0007] The multi-level pore structure effectively achieves a balance between high elasticity and high equivalent thermal conductivity. Generally speaking, the higher the orientation of the graphene sheet, the better the thermal conductivity in that direction, but due to the rigidity of the graphene sheet, its compression rate is significantly reduced, and it even appears inelastic. Excessive rigidity will lead to the existence of an air layer between the material interfaces, resulting in a significant increase in the interfacial thermal resistance. Correspondingly, the introduction of a porous structure can effectively improve the compression elasticity, but the vertical thermal conductivity is also greatly reduced. In this patent, the 10~50nm holes are mainly present in the wrinkles in the graphene sheet, which has little effect on the vertical thermal conductivity, but can improve the freedom of the graphene sheet, reduce the rigidity of the graphene sheet while ensuring the orientation of the graphene sheet in the vertical direction; the 1~10μm holes are mainly present between the graphene sheets, forming small air bags to prevent the overall structure from being crushed and help the material rebound; the 100~300μm holes are scattered throughout the membrane, providing space for the compression deformation of the graphene sheet. The reasonable density range is to avoid irreversible deformation of graphene sheets caused by excessive pores at low density, and high rigidity caused by high density. The thermal impedance of the material is significantly lower than that of existing thermal conductive silicone gaskets (basically 0.3 K cm 2 / W or more), it has significant advantages in achieving efficient vertical heat dissipation performance.

[0008] Furthermore, the thickness of the graphene sheet is between 20 and 500 nm, and the oxygen content is less than 0.5%. The reasonable thickness of the graphene sheet is to obtain high flexibility and high compression resilience, so as to fill the interface gap by compression in thermal interface applications, avoid the introduction of air layer by rigid contact, and effectively reduce the interface thermal resistance. Too low thickness of the graphene sheet will lead to insufficient compression strength and difficulty in rebound after compression. Too high thickness will lead to excessive rigidity of the graphene sheet and cannot complete compression to achieve effective filling. Controlling the oxygen content below 0.5% is to reduce graphene defects and improve the intrinsic thermal conductivity.

[0009] The second technical solution of the present invention is to provide a method for preparing a graphene thermal interface material with a multi-level pore structure, which specifically comprises the following steps: (1) dissolving aminoguanidine carbonate in deionized water to form an aminoguanidine carbonate solution with a concentration of 20 wt %; (2) adding 0.5 to 2 parts by weight of the aminoguanidine carbonate solution obtained in step (1) to 100 parts by weight of a 2 wt% graphene oxide solution, and stirring to mix well; (3) forming a film using the mixed solution obtained in step (2), and drying at room temperature for 10 to 24 hours to obtain a dry film with a thickness of 0.05 to 0.5 mm; (4) heating the dried film obtained in step (3) at a temperature below 250° C. for foaming, with the highest temperature being between 200° C. and 250° C., to obtain a preliminary foamed film; (5) The preliminary foamed film obtained in step (4) is placed in an argon atmosphere, heated to 2800-3200°C at 5°C / min for high temperature treatment for 0.5-3 h to obtain a graphene thermal interface material with a multi-level pore structure.

[0010] The use of aminoguanidine carbonate as a reducing agent in step (1) avoids the use of conventional hydrazine hydrate reducing agent, which is greener, more environmentally friendly and safer (also mentioned in patent CN103420365B). On the other hand, the phenomenon of aminoguanidine carbonate reducing graphene oxide is also very different from that of hydrazine hydrate, which is reflected in the fact that the reduction rate of aminoguanidine carbonate itself is relatively slow, and the gas generated by the reaction is slowly released. Unlike hydrazine hydrate, a large amount of gas is not generated in a short time, which causes the volume of the graphene oxide film to expand violently. Therefore, after aminoguanidine carbonate and graphene oxide are mixed, no violent reduction reaction will occur in a short period of time, the overall stability of the solution is good, and coating can be performed; during the coating process, wrinkles will appear on the graphene film, and in the subsequent film-forming and drying process, aminoguanidine carbonate and graphene oxide undergo a slow reduction reaction, so that cross-linking occurs between graphene oxide sheets, and primary pores are formed in the wrinkles as water evaporates; in low-temperature heat treatment, aminoguanidine carbonate decomposes at 50-100°C to produce gas, which forms secondary pores, and above 100°C, graphene oxide further loses oxygen-containing groups to form gas that promotes the formation of tertiary pores; finally, the pore structure further develops under high-temperature treatment to form a final multi-level pore structure.

[0011] Furthermore, the average thickness of the graphene oxide in step (2) is between 0.8 and 100 nm.

[0012] Furthermore, the film forming method in step (3) is a casting method, a blade coating method, or a spin coating method.

[0013] Furthermore, the heating and foaming method in step (4) is to increase the temperature to 200-250°C in an oven at 2-5°C / min and keep the temperature for 1-3 hours.

[0014] Furthermore, the heating and foaming method in step (4) can also be to increase the temperature to 50°C in an oven at 2°C / min and keep it at that temperature for 1-3 hours, and then increase the temperature to 200-250°C at 5°C / min and keep it at that temperature for 1-3 hours.

[0015] The decomposition temperature of aminoguanidine carbonate is about 50-100°C, and a thermal decomposition reaction occurs at this temperature. Heating to 200°C can rapidly thermally decompose aminoguanidine carbonate, generate gas, and introduce a porous structure. Heating to 50°C first to keep warm is to further reduce aminoguanidine carbonate and graphene oxide in the low temperature zone, and then heating to decompose, so as to obtain a richer mesoporous structure.

[0016] Beneficial effects of the present invention: (1) Unique multi-level pore structure: Based on the conventional graphene membrane, a multi-level pore structure mainly distributed in 10~50nm, 1~10μm and 100~300μm is introduced, making the graphene thermal interface material light, compression-resistant and highly flexible. The wrinkled graphene membrane builds a three-dimensional thermal conductive network, ensuring efficient heat transfer in the vertical direction.

[0017] (2) Lower interface thermal resistance: The wrinkled and porous graphene microstructure is conducive to filling the gaps between the heating interfaces. The graphene sheets effectively fill the tiny undulations on the surface of the heating surface, significantly reducing the air layer and lowering the interface thermal resistance. The overall equivalent thermal conductivity is higher than that of conventional thermal pads.

[0018] (3) High cost-effectiveness: By making simple improvements on the conventional graphene film preparation process, high-performance graphene thermal interface materials can be prepared in batches with low equipment requirements.

[0019] (4) Environmentally friendly: The main raw materials are only water, graphene oxide and aminoguanidine carbonate. No highly toxic and highly polluting chemical reagents are involved. Wastewater can be simply treated to meet discharge requirements, which puts less pressure on the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a SEM cross-sectional view of the graphene thermal interface material obtained in Example 1; Figure 2 This is a size distribution diagram of the graphene thermal interface material obtained in Example 1; Figure 3 The thermal impedance curves of the graphene thermal interface material obtained in Example 1 under different pressures; Figure 4 The thermal impedance performance of the graphene thermal interface material obtained in Example 1 after repeated disassembly and assembly for 5 times. DETAILED DESCRIPTION

[0021] The embodiments of the present invention are further described below with reference to a plurality of embodiments.

[0022] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0023] The raw materials used in the present invention, unless otherwise specified, are conventional commercially available products; the methods used in the present invention, unless otherwise specified, are conventional methods in the art.

[0024] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0025] In addition, the technical terms involved in the present invention are explained as follows: As is common knowledge in the art, the pore size distribution is obtained by mercury intrusion testing. The horizontal axis of the pore size distribution curve is the pore size, and the vertical axis is the amount of mercury intrusion (quantitative representation of volume ratio). Thermal impedance is the sum of the thermal resistance of the material itself and the thermal resistance between the contact surfaces. It is tested using the ASTM D 5470 method, and the equipment is the LW-9389MD interface material thermal resistance and thermal conductivity coefficient meter.

[0026] Cast film coating is a process that forms a uniform film by pouring a liquid coating material onto a substrate and utilizing its fluidity. Scraping coating is a method that uses a scraper to evenly coat a liquid coating material onto a substrate, removes excess material by moving the scraper, and forms a film of a certain thickness. Spin coating is a process that forms a film by rotating the substrate so that the liquid coating material is evenly distributed on the surface of the substrate due to centrifugal force. After the graphene oxide film is prepared by the above three methods, a wrinkled structure will spontaneously form in the graphene oxide sheet as water evaporates during the drying process, and the wrinkled graphene oxide sheets will stack to form a dry graphene oxide film.

[0027] Example 1 (1) dissolving aminoguanidine carbonate in deionized water to form an aminoguanidine carbonate solution having a concentration of 20 wt %; (2) adding 2 parts by weight of the aminoguanidine carbonate solution obtained in step (1) to 100 parts by weight of a 2 wt% graphene oxide solution, and stirring to mix evenly; wherein the graphene oxide has a thickness of 0.8 nm; (3) forming a film by a casting method using the mixed solution obtained in step (2), and drying at room temperature for 12 hours to obtain a dry film with a thickness of 0.05 mm; (4) placing the dried film obtained in step (3) in an oven for heating and foaming, raising the temperature to 200°C at 2°C / min, and keeping the temperature for 1 hour to obtain a preliminary foamed film; (5) The preliminary foamed film obtained in step (4) is placed in an argon atmosphere, and the temperature is increased to 2800°C at 5°C / min for high temperature treatment for 1 h to obtain a graphene thermal interface material with a multi-level pore structure.

[0028] The microstructure of the obtained graphene thermal interface material is as follows: Figure 1 As shown, it is composed of wrinkled graphene sheets with pore structures of different pore sizes. The overall thickness of the material is 0.3 mm and the density is 0.12 g / cm 3 , including pore structures with sizes mainly distributed in 10~50nm, 1~10μm and 100~300μm (size distribution such as Figure 2 The average thickness of the graphene sheet is 20 nm and the oxygen content is 0.01%. The thermal impedance of the material under different pressures is shown in Figure 3 As shown in Figure 2, as the pressure increases, the thermal impedance decreases, and the thermal resistance is 0.129 K cm at 50 psi. 2 / W, significantly lower than conventional thermal pads (generally 0.5~2 K cm 2 / W). And if Figure 4 The material can be disassembled and assembled repeatedly, and the thermal impedance change does not exceed 5% within 5 times of disassembly and assembly. The specific performance is shown in Table 1.

[0029] Example 2 (1) dissolving aminoguanidine carbonate in deionized water to form an aminoguanidine carbonate solution having a concentration of 20 wt %; (2) adding 0.5 parts by weight of the aminoguanidine carbonate solution obtained in step (1) to 100 parts by weight of a 2 wt% graphene oxide solution, and stirring to mix evenly; wherein the graphene oxide has a thickness of 0.8 nm; (3) forming a film by a casting method using the mixed solution obtained in step (2), and drying at room temperature for 24 hours to obtain a dry film with a thickness of 0.05 mm; (4) placing the dried film obtained in step (3) in an oven for heating and foaming, raising the temperature to 250°C at 2°C / min, and keeping the temperature for 3 hours to obtain a preliminary foamed film; (5) The preliminary foamed film obtained in step (4) is placed in an argon atmosphere, and the temperature is increased to 2800°C at 5°C / min for high temperature treatment for 3 h to obtain a graphene thermal interface material with a multi-level pore structure.

[0030] The obtained graphene thermal interface material is composed of wrinkled graphene sheets with an overall thickness of 0.2 mm and a density of 0.16 g / cm 3, including pore structures with sizes mainly distributed in 10~50nm, 1~10μm and 100~300μm, the average thickness of the graphene sheet is 20 nm, the oxygen content is 0.01%, and the specific properties are shown in Table 1.

[0031] Example 3 (1) dissolving aminoguanidine carbonate in deionized water to form an aminoguanidine carbonate solution having a concentration of 20 wt %; (2) adding 0.5 parts by weight of the aminoguanidine carbonate solution obtained in step (1) to 100 parts by weight of a 2 wt% graphene oxide solution, and stirring to mix evenly; wherein the graphene oxide has a thickness of 10 nm; (3) forming a film by a casting method using the mixed solution obtained in step (2), and drying at room temperature for 10 hours to obtain a dry film with a thickness of 0.1 mm; (4) placing the dried film obtained in step (3) in an oven for heating and foaming, heating the film to 50°C at 2°C / min and keeping the temperature for 1 hour, then heating the film to 250°C at 5°C / min and keeping the temperature for 1 hour, to obtain a preliminary foamed film; (5) The preliminary foamed film obtained in step (4) is placed in an argon atmosphere, and the temperature is increased to 2800° C. at 5° C. / min for high temperature treatment for 0.5 h to obtain a graphene thermal interface material with a multi-level pore structure.

[0032] The obtained graphene thermal interface material is composed of wrinkled graphene sheets with an overall thickness of 0.2 mm and a density of 0.32 g / cm 3 , including pore structures with sizes mainly distributed in 10~50nm, 1~10μm and 100~300μm, the average thickness of the graphene sheet is 80 nm, the oxygen content is 0.01%, and the specific properties are shown in Table 1.

[0033] Example 4 (1) dissolving aminoguanidine carbonate in deionized water to form an aminoguanidine carbonate solution having a concentration of 20 wt %; (2) adding 0.5 parts by weight of the aminoguanidine carbonate solution obtained in step (1) to 100 parts by weight of a 2 wt% graphene oxide solution, and stirring to mix evenly; wherein the graphene oxide has a thickness of 100 nm; (3) using the mixed solution obtained in step (2) to form a film by a doctor blade method, and drying at room temperature for 24 hours to obtain a dry film with a thickness of 0.5 mm; (4) placing the dried film obtained in step (3) in an oven for heating and foaming, heating the film to 50°C at 2°C / min and keeping the temperature for 3 h, then heating the film to 200°C at 5°C / min and keeping the temperature for 3 h, to obtain a preliminary foamed film; (5) The preliminary foamed film obtained in step (4) is placed in an argon atmosphere, and the temperature is increased to 2800°C at 5°C / min for high temperature treatment for 1 h to obtain a graphene thermal interface material with a multi-level pore structure.

[0034] The obtained graphene thermal interface material is composed of wrinkled graphene sheets with an overall thickness of 2 mm and a density of 0.16 g / cm 3 , including pore structures with sizes mainly distributed in 10~50nm, 1~10μm and 100~300μm, the average thickness of the graphene sheet is 500 nm, the oxygen content is 0.02%, and the specific properties are shown in Table 1.

[0035] Example 5 (1) dissolving aminoguanidine carbonate in deionized water to form an aminoguanidine carbonate solution having a concentration of 20 wt %; (2) adding 2 parts by weight of the aminoguanidine carbonate solution obtained in step (1) to 100 parts by weight of a 2 wt% graphene oxide solution, and stirring to mix evenly; wherein the graphene oxide has a thickness of 0.8 nm; (3) using the mixed solution obtained in step (2) to form a film by spin coating, and drying at room temperature for 24 hours to obtain a dry film with a thickness of 0.05 mm; (4) placing the dried film obtained in step (3) in an oven for heating and foaming, raising the temperature to 250°C at 5°C / min, and keeping the temperature for 3 hours to obtain a preliminary foamed film; (5) The preliminary foamed film obtained in step (4) is placed in an argon atmosphere, and the temperature is increased to 3200° C. at a rate of 5° C. / min for high temperature treatment for 0.5 h to obtain a graphene thermal interface material with a multi-level pore structure.

[0036] The obtained graphene thermal interface material is composed of wrinkled graphene sheets with an overall thickness of 0.45 mm and a density of 0.08 g / cm 3 , including pore structures with sizes mainly distributed in 10~50nm, 1~10μm and 100~300μm, the average thickness of the graphene sheet is 20 nm, the oxygen content is 0.01%, and the specific properties are shown in Table 1.

[0037] Comparative Example 1 (1) dissolving hydrazine hydrate in deionized water to form a hydrazine hydrate solution with a concentration of 20 wt%; (2) adding 0.5 parts by weight of the hydrazine hydrate solution obtained in step (1) to 100 parts by weight of a 2 wt% graphene oxide solution, and stirring to mix evenly; wherein the graphene oxide has a thickness of 10 nm; (3) using the mixed solution obtained in step (2) to form a film by a doctor blade method, and drying at room temperature for 10 hours to obtain a dry film with a thickness of 0.1 mm; (4) placing the dried film obtained in step (3) in an oven for heating and foaming, heating the film to 50°C at 2°C / min and keeping the temperature for 1 hour, then heating the film to 200°C at 5°C / min and keeping the temperature for 1 hour, to obtain a preliminary foamed film; (5) The preliminary foamed film obtained in step (4) is placed in an argon atmosphere, heated to 2800°C at 5°C / min for 0.5 h to obtain a graphene thermal interface material with a porous structure.

[0038] During the preparation process, it was found that during the mixing process in step (2), the viscosity of the solution increased significantly with stirring, and the fluidity became poor. During the coating process in step (3), the operation was difficult and continuous film formation was not possible. The overall thickness of the obtained partial graphene thermal interface material was 0.13 mm and the density was 0.5 g / cm 3 The average thickness of the graphene sheet is 1~3 μm, the oxygen content is 0.01%, and the specific properties are shown in Table 1.

[0039] It can be found that the pore volume of 10-50 nm is much larger than that of 1-10 μm and 100-300 μm. This is because the reducibility of hydrazine hydrate is much higher than that of aminoguanidine carbonate. The reduction reaction begins in step (2), causing the graphene oxide to form a wrinkled structure in the solution. After coating, a pore structure is formed in the wrinkles. At the same time, due to the strong reduction reaction of graphene oxide, the graphene sheets are stacked. Therefore, no obvious gas is generated during the heating in step (4), and the 100-300 μm macropores generated in the high temperature treatment in step (5) are also significantly less than those in Examples 1-5. This relatively dense structure has lower compressibility and higher thermal impedance, and is not suitable for use as a thermal interface.

[0040] Table 1 Summary of performance of various embodiments

[0041] The above embodiments describe in detail the structure, features and effects of the present invention. The above are only preferred embodiments of the present invention. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which do not exceed the scope covered by the specification, should be within the protection scope of the present invention.

Claims

1. A graphene thermal interface material with a multi-level pore structure, characterized in that: It is composed of wrinkled graphene sheets with an overall thickness of 0.2~2 mm and a density of 0.08~0.32 g / cm 3 The graphene thermal interface material comprises primary pores with a size of 10 to 50 nm, secondary pores with a size of 1 to 10 μm, and tertiary pores with a size of 100 to 300 μm; the primary pores exist in the wrinkles within the graphene sheets, and the secondary and tertiary pores exist between the graphene sheets.

2. The thermal interface material according to claim 1, characterized in that: In the graphene thermal interface material, the volume proportions of the primary pores, secondary pores and tertiary pores are 16% to 28%, 35% to 42% and 20% to 28% respectively.

3. The thermal interface material according to claim 1, characterized in that: The graphene sheet has a thickness of 20-500 nm and an oxygen content of less than 0.5%.

4. A method for preparing the graphene thermal interface material according to claim 1, characterized in that: The following steps are involved: (1) dissolving aminoguanidine carbonate in deionized water to form an aminoguanidine carbonate solution with a concentration of 20 wt %; (2) adding 0.5 to 2 parts by weight of the aminoguanidine carbonate solution obtained in step (1) to 100 parts by weight of a 2 wt% graphene oxide solution, and stirring to mix well; (3) forming a film using the mixed solution obtained in step (2), and drying at room temperature for 10 to 24 hours to obtain a dry film with a thickness of 0.05 to 0.5 mm; (4) heating the dried film obtained in step (3) at a temperature below 250° C. for foaming to obtain a preliminary foamed film; (5) The preliminary foamed film obtained in step (4) is placed in an argon atmosphere, heated to 2800-3200°C at 5°C / min for high temperature treatment for 0.5-3 h to obtain a graphene thermal interface material with a multi-level pore structure.

5. The preparation method according to claim 4, characterized in that: The average thickness of the graphene oxide in step (2) is between 0.8 and 100 nm.

6. The preparation method according to claim 4, characterized in that: The film forming method in step (3) is casting, blade coating or spin coating.

7. The preparation method according to claim 4, characterized in that: The heating and foaming method in step (4) is to increase the temperature to 200-250°C at 2-5°C / min and keep the temperature for 1-3h.

8. The preparation method according to claim 4, characterized in that: The heating foaming method in step (4) is to increase the temperature to 50°C in an oven at 2°C / min and keep it at that temperature for 1-3 hours, then increase the temperature to 200-250°C at 5°C / min and keep it at that temperature for 1-3 hours.

Citation Information

Patent Citations

  • Graphene preparation method

    CN103420365A

  • Thermal interface material and preparation method thereof

    CN111572119A

  • High-conductivity and high-thermal-conductivity graphene film as well as preparation method and application thereof

    CN116675221A

  • High-elasticity low-thermal-resistance graphene thermal interface material and preparation method thereof

    CN117566730A

  • Preparation method of high-performance graphene-based thermal interface material

    CN117887428A

Cited By

  • Thermal interface material with high compression resilience and preparation method thereof

    CN119953034A